Status, Values and Challenges in Chiropterans Conservation - Niraula, Richa; Jha, Sunny (The Initiation, 2011)
Chiropterans (Bats) comprise 1,001 species in total and are distributed worldwide. These have high ecological and economical value. Nepal comes under the highlighted subregion in the South Asia owing to the abundance of bats over here. Yet, very few detailed analyses have been done, and the exact status including biological habits are still not properly documented. This has made already vulnerable population more vulnerable with a continuous threat that some valuable species might get lost even before realizing. This paper provides insight to the status of bats in Nepal, the challenges present in their conservation and the ways ahead. DOI: http://dx.doi.org/10.3126/init.v4i0.5542 The Initiation Vol.4 2011 103-110